CLIMATE AND FINANCE RISK ASSESSMENTS OF FIVE AGRIBUSINESSES USING AI-TOOLS - Muthio Muoki, Nicole; Hauke, Dahl; Peterson, Nathanial Richard (2025)
Agribusinesses across Africa face mounting financial and operational risks, intensified by climate change. Many small and medium enterprises operate with limited capital, narrow revenue bases, and exposure to drought, fuel, and currency shocks. These intertwined risks are hard for investors to assess, while traditional risk advisory services remain costly and out of reach for early-stage firms. This report presents AI-assisted risk assessments as a scalable, low-cost solution. Five anonymized agribusinesses, spanning honey, rice, solar irrigation, poultry inputs, and oilseed processing, were analyzed to identify financial, climate, and organizational vulnerabilities. The results reveal shared risks but also adaptive practices that enhance resilience. By standardizing and automating the assessment process, the AI tool enables faster, more transparent evaluation of enterprise risk profiles. The approach reduces transaction costs for investors and strengthens the capacity of agribusinesses to attract climate-aligned finance and build long-term resilience in Africa’s food systems.